Recoding of the Vesicular Stomatitis Virus L Gene by Computer-Aided Design Provides a Live, Attenuated Vaccine Candidate - Bingyin Wang (American Society for Microbiology, 2015)
ABSTRACT Codon pair bias (CPB), which has been observed in all organisms, is a neglected genomic phenomenon that affects gene expression. CPB results from synonymous codons that are paired more or less frequently in ORFeomes regardless of codon bias. The effect of an individual codon pair change is usually small, but when it is amplified by large-scale genome recoding, strikingly altered biological phenotypes are observed. The utility of codon pair bias in the development of live attenuated vaccines was recently demonstrated by recodings of poliovirus (a positive-strand RNA virus) and influenza virus (a negative-strand segmented RNA virus). Here, the L gene of vesicular stomatitis virus (VSV), a nonsegmented negative-sense RNA virus, was partially recoded based on codon pair bias. Totals of 858 and 623 silent mutations were introduced into a 5′-terminal segment of the viral L gene (designated L1) to create sequences containing either overrepresented or underrepresented codon pairs, designated L1sdmax and L1min, respectively. Analysis revealed that recombinant VSV containing the L1min sequence could not be recovered, whereas the virus with the sdmax sequence showed a modest level of attenuation in cell culture. More strikingly, in mice the L1sdmax virus was almost as immunogenic as the parental strain but highly attenuated. Taken together, these results open a new road to attain a balance between VSV virulence and immunogenicity, which could serve as an example for the attenuation of other negative-strand, nonsegmented RNA viruses. IMPORTANCE Vesicular stomatitis virus (VSV) is the prototypic rhabdovirus in the order Mononegavirales. A wide range of human pathogens belong to this family. Using a unique computer algorithm and large-scale genome synthesis, we attempted to develop a live attenuated vaccine strain for VSV, which could be used as an antigen delivery platform for humans. Recombinant VSVs with distinct codon pair biases were rationally designed, constructed, and analyzed in both cell culture and an animal model. One such recombinant virus, L1sdmax, contained extra overrepresented codon pairs in its L gene open reading frame (ORF) and showed promise as an effective vaccine candidate because of a favorable balance between virulence and immunogenicity. Our study not only contributes to the understanding of the underlying mechanism of codon pair bias but also may facilitate the development of live attenuated vaccines for other viruses in the order Mononegavirales.